2018
DOI: 10.1097/nur.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring Lifestyle Behavior in Overweight and Obese Pregnant Women

Abstract: Self-monitoring is a promising approach to weight management for overweight and obese pregnant women. However, healthcare providers should be aware that, although women may identify several benefits to self-monitoring, for some women, consistently trying to track their behaviors is stressful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Despite the barriers and challenges participants encountered at the beginning of the intervention, they were able to identify strategies from various resources to overcome obstacles and cope with them. The identified barriers (eg, technology difficulties and lack of time) are similar to those reported previously [ 39 ]. Our study found that the involvement of family and friends, as well as the assistance from an intervention program could help overcome barriers and facilitate technology-assisted self-monitoring.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Despite the barriers and challenges participants encountered at the beginning of the intervention, they were able to identify strategies from various resources to overcome obstacles and cope with them. The identified barriers (eg, technology difficulties and lack of time) are similar to those reported previously [ 39 ]. Our study found that the involvement of family and friends, as well as the assistance from an intervention program could help overcome barriers and facilitate technology-assisted self-monitoring.…”
Section: Discussionsupporting
confidence: 79%
“…Further, at the end of the 6-month discussion, participants seemed more comfortable and integrated in using technology-assisted self-monitoring of lifestyle behaviors and health indicators. The barriers of engaging in technology-assisted self-monitoring (eg, technology difficulties) have been extensively studied [ 34 , 38 , 39 ]. The learning curve of using technology-assisted self-monitoring for disease management, however, has rarely been comprehensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of monitoring varies between individuals and over time, and as a result, it is not evident how frequently users should be encouraged to self-monitor. In fact, encouraging high rates of tracking could potentially worsen stress and cause harm [50]. Further work evaluating different self-monitoring frequencies is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional education raised the awareness of healthy pregnancy diets [ 75 ], influencing a more restrictive attitude towards food intake [ 76 ]. Weekly weight monitoring facilitates a real-time understanding of weight changes, promoting proactive restrained eating for better weight control [ 77 ]. Reminders of weight-gain standards emphasized healthy weight management goals, guiding pregnant women to consciously choose healthier eating habits [ 78 ].…”
Section: Discussionmentioning
confidence: 99%